Instrução como estratégia de enfrentamento para a realização de curativo sem sedação em enfermaria com crianças vítimas de queimadura - OLIVEIRA, Fabiana Pereira Sabino de (Universidade Federal do Pará, 2014)
One may define “burn” as the resulting picture or the outcome of a direct or indirect action of heat, chemical compounds or electricity over the human organic structure. Some studies point out children as the majority of victims. Procedures, inherent to the process of recovery, are known to be particularly painful. The frequency of invasive medical procedures on burn-victims, favors the production of concurrent behaviors from the child and can lead to the generalization of the aversive feature of the invasive procedure to stimuli existing in the environment, thus justifying studies over the effectiveness of such invasive interventions. The research was divided into two studies with specific objectives. Study 1 (n = 5): to characterize behaviors of children which are burn-victims, produced during curative procedures without sedation in wards and to compare the frequency of concurrent and non-concurrent behaviors generated by these children in two consecutive sessions of this procedure. Study 2 (n = 2): to analyze the effects of the use of instruction on the frequency of concurrent and non-concurrent behaviors in children which are burn-victims during the curative procedure without sedation in wards. Seven children (four boys and three girls, ages 7-12) victims of burns on body lower areas inferior to 70% and their companions, selected from a Burn Treatment Center (BTC) participated. The following were used as instruments: (a) Health Care Team Consultation Protocol, (b) Child Behavioral Check List (CBCL 6-18 years), (c) Guide Book for interviewing the child, (d) Observation scale of behavioral distress OSBD, (e) Scale to evaluate the child’s facial pain perception and (f) Instruction Manual on curative procedures. In Study 1, it was noticed a higher frequency of concurrent behavior over the non- concurrent one in two sessions of curative procedures. In Study 2, upon using the Instruction Manual, it was noticed a statistically significant reduction in the frequency of the concurrent behavior Whimpering (p-value = 0.0447) and a significant increase (p-value = 0.0324) in the frequency of non-concurrent behavior Assistant in the implementation of the procedure. There was a significant correlation (p-value = 0.0066) between the frequency of non-concurrent behaviors among children in Study 1 and those who participated in Study 2, therefore suggesting that the intervention was effective in increasing the frequency of non-concurrent behaviors in children participating in Study 2.